Managing innovative projects - Webb, Alan. (London ; New York : Chapman & Hall, 1994)
Managing Innovative Projects is a comprehensive guide to the tools and techniques of contemporary project management. It will prove an invaluable reference for practising managers and professionals in new product development. Alan Webb has written an engaging and clear description of the many techniques used in industry today, from the technical and contractual to the managerial issues essential to innovative project management. New methods are explained in detail. The managerial applications of today's methodologies are enhanced with worked examples, taken from a wide range of industries, which illustrate many common pitfalls and problems. Managing Innovative Projects will give you the appropriate skills and techniques to manage the challenging and complex issues in contemporary project management, and will help you to bring your project to a successful conclusion.
1. Introduction -- 2. Innovation and the creation of new products -- 3. Getting organized -- 4. Planning: the way ahead -- 5. Success by design -- 6. The cost and value of products -- 7. Managing the flow of materials -- 8. Progress, performance and control -- 9. Planning and implementing the production programme -- 10. The economics of projects -- 11. Managing the risks -- 12. Some commercial aspects -- 13. Software for the Project Manager -- Appendix: Products and vendors.
Includes bibliographical references (p. 375-376) and index.
Keywords: Technological innovations -- Management; Project management